Droit du transport de passagers et responsabilité civile - Langer, Léhi (Université Jean Monnet, 2025)
À l'heure d'une mobilité toujours plus intense, le transport de passagers occupe une place essentielle dans nos sociétés. Son développement continu, porté par les progrès techniques, l'essor du tourisme et les politiques publiques, s'accompagne de nouveaux défis juridiques, en particulier en matière de responsabilité civile. Cette thèse interroge les transformations du droit de la responsabilité civile à la lumière des règles spécifiques au transport de passagers, dans un contexte marqué par une forte influence du droit européen et international.L'étude révèle un double mouvement : l'affirmation de droits autonomes pour les passagers d'une part, et la reconfiguration du rôle de la responsabilité civile d'autre part. Le contrat de transport, bien que central, cède partiellement sa place à des droits issus directement de normes européennes. Cette évolution complexifie la distinction entre responsabilité contractuelle et délictuelle, au profit de mécanismes hybrides de réparation et de garantie.Face à la diversité des sources et des régimes applicables selon les modes de transport, la cohérence du droit devient un enjeu majeur. La thèse propose une clarification des obligations du transporteur et une délimitation précise des notions clés telles que l'accident, le dommage corporel ou les circonstances extraordinaires. Elle appelle aussi à repenser certains fondements, notamment à l'aune des transports autonomes, des plateformes numériques et des défis posés par la multimodalité.En définitive, le droit du transport de passagers apparaît comme un champ d'expérimentation de la responsabilité civile contemporaine. Il invite à trouver un nouvel équilibre entre protection des passagers, efficacité du système et sécurité juridique des opérateurs. In an era of ever-increasing mobility, passenger transport plays a vital role in our societies. Its continuous development—driven by technological progress, the growth of tourism, and public policy—is accompanied by new legal challenges, particularly regarding civil liability. This thesis examines the evolution of civil liability in light of the specific rules governing passenger transport, within a context heavily influenced by European and international law.The study reveals a dual dynamic: on the one hand, the emergence of autonomous rights for passengers; on the other, a redefinition of the role of civil liability. While the transport contract remains central, it is increasingly complemented—if not partially replaced—by rights granted directly through European regulations. This shift complicates the traditional distinction between contractual and tortious liability, giving rise to hybrid mechanisms of reparation and protection.Given the diversity of sources and legal regimes across different transport modes, legal coherence becomes a major concern. The thesis proposes a clarification of the carrier's obligations and a precise delineation of key concepts such as "accident", "bodily harm", and "extraordinary circumstances". It also calls for a reconsideration of certain legal foundations, especially in the face of autonomous transport, digital platforms, and the challenges of multimodality.Ultimately, passenger transport law emerges as a testing ground for modern civil liability. It invites a new balance between passenger protection, system efficiency, and legal certainty for operators.
Issue: 2025UJMO0054
Keywords: Contract; Contrat; Droits; Liability; Passager; Passenger; Protection; Responsabilité; Rights; Transport; Transportation

Sürdürülebilir tedarik zinciri uygulamaları ve ev dışında teslimatın e-memnuniyet, e-sadakat ve ödeme isteği üzerine etkisi: Tüketicilere yönelik karma yöntem uygulaması - Teki̇n, Makber (Akdeniz Üniversitesi, 2025)
Dijitalleşmenin hız kazandığı ve tüketici davranışlarının dönüşüme uğradığı günümüz e-ticaret ortamında, özellikle Covid-19 pandemisi sonrası çevrimiçi alışverişin yaygınlaşması sürdürülebilir lojistik uygulamalarının önemini artırmıştır. Artan sipariş hacmi, çevresel etkiler, karbon salımı ve teslimat sürelerine ilişkin beklentiler; daha verimli, esnek ve çevre dostu teslimat çözümlerine olan ihtiyacı gündeme getirmiştir. Bu bağlamda ev dışında teslimat gibi alternatif lojistik hizmetler ile sosyal, çevresel ve ekonomik sürdürülebilirlik yaklaşımları, tüketici davranışlarını etkileme potansiyeli taşıyan önemli değişkenler olarak öne çıkmaktadır. Bu doğrultuda tezin amacı, sürdürülebilir tedarik zinciri uygulamaları ile ev dışında teslimat modellerinin, e-memnuniyet, e-sadakat ve ödeme isteği üzerindeki etkilerini tüketiciler üzerinden incelemektir. Araştırma, açıklayıcı sıralı karma yöntem stratejisi ile yürütülmüştür. İlk aşamada 300'ü aşkın tüketiciden anket yoluyla nicel veriler toplanmış, ardından ikinci aşamada 27 katılımcı ile yapılan yarı yapılandırılmış görüşmeler aracılığıyla nitel veriler elde edilmiştir. Nicel veriler yapısal eşitlik modellemesiyle, nitel veriler ise tematik analiz yöntemiyle değerlendirilmiştir. Bulgular, özellikle sosyal ve çevresel sürdürülebilirlik boyutlarının e-memnuniyet üzerinde ve ekonomik ve çevresel sürdürülebilirlik boyutlarının ise e-sadakat üzerinde anlamlı etkiler yarattığı yönündedir. Sürdürülebilirliğin üç boyutu da ödeme istekliliği üzerinde anlamlı ve pozitif bir etki yaratmamıştır. Ekonomik sürdürülebilirlik boyutu ise tüketiciler tarafından doğrudan algılanamadığı için memnuniyet üzerinde anlamlı bir etki göstermemiştir. Ev dışında teslimat uygulamalarının esneklik, zaman tasarrufu ve erişilebilirlik gibi avantajlar sunarak e-memnuniyeti ve ödeme isteğini artırdığını göstermektedir. Son olarak e-memnuniyetin, e-sadakati ve e-sadakatin, ödeme isteğini pozitif yönde anlamlı etkilediği sonucuna ulaşılmıştır. Bu tez, sürdürülebilir tedarik zinciri yönetimi, ev dışında teslimat ve e-ticarette tüketici memnuniyeti, tüketici sadakati ve ödeme isteğini bütüncül biçimde ele alan özgün bir model sunmaktadır. Sürdürülebilir tedarik zinciri uygulamaları ve ev dışında teslimat hizmetlerinin tüketici davranışları üzerindeki etkilerini açıklamak amacıyla Sosyal Kimlik Teorisi (SIT), Yeşil Tüketici Davranışı Yaklaşımı ve destekleyici olarak Yeniliğin Yayılımı Teorisi (YYT) çerçevesinde şekillenen kuramsal yapı, sürdürülebilir uygulamaların tüketicilerdeki karşılığını açıklamaya yardımcı olmuştur. Ayrıca bu çalışma, Türkiye örneğinde sürdürülebilir teslimat hizmetlerine yönelik farkındalık düzeyini ve bu hizmetlerin e-memnuniyet, e-sadakat ve ödeme davranışları üzerindeki etkilerini analiz ederek hem akademik literatüre hem de pratik lojistik ve pazarlama stratejilerine katkı sunması beklenmektedir. In today's rapidly evolving e-commerce landscape, shaped by accelerated digitalization and shifting consumer behaviors, the widespread adoption of online shopping - particularly in the aftermath of the Covid-19 pandemic - has amplified the significance of sustainable logistics practices. Increasing order volumes, environmental impacts, carbon emissions, and heightened expectations regarding delivery times have underscored the need for more efficient, flexible, and eco-friendly delivery solutions. In this context, out-of-home delivery services and the dimensions of social, environmental, and economic sustainability have emerged as key variables with the potential to influence consumer behavior. Accordingly, the purpose of this dissertation is to examine the effects of sustainable supply chain practices and out-of-home delivery models on e-satisfaction, e-loyalty, and willingness to pay, through the lens of consumer perceptions. The research adopts an explanatory sequential mixed-methods design. In the first phase, quantitative data were collected via a survey administered to over 300 consumers; in the second phase, qualitative data were obtained through semi-structured interviews conducted with 27 participants. The quantitative data were analyzed using structural equation modeling, while the qualitative data were evaluated through thematic analysis. The findings indicate that the social and environmental dimensions of sustainability have a significant impact on e-satisfaction, while the economic and environmental dimensions significantly influence e-loyalty. None of the three dimensions of sustainability were found to have a significant and positive effect on willingness to pay. The economic dimension of sustainability did not show a significant effect on satisfaction, likely because it is not directly perceived by consumers. Out-of-home delivery practices were found to enhance e-satisfaction and willingness to pay by offering advantages such as flexibility, time savings, and accessibility. Finally, the results revealed that e-satisfaction has a positive and significant effect on e-loyalty, and e-loyalty, in turn, significantly and positively affects willingness to pay. This study aims to develop an original and integrative model that examines sustainable supply chain management, out-of-home delivery, and key consumer outcomes in e-commerce, namely e-satisfaction, e-loyalty, and willingness to pay. Grounded in the Social Identity Theory (SIT), the Green Consumer Behavior Approach, and supported by the Diffusion of Innovations Theory (DOI), the proposed theoretical framework explains how sustainable supply chain practices and out-of-home delivery services shape consumer behavior. Moreover, by investigating the level of awareness of sustainable delivery services in the Turkish context and analyzing their effects on e-satisfaction, e-loyalty, and payment behavior, this research is expected to provide significant contributions to both academic literature and practical implications for logistics and marketing strategies.
Keywords: E-commerce; E-ticaret; Ev Dışı Teslimat; Green Consumer Behavior; Karma Yöntem; Mixed Methods; Out-of-Home Delivery; Sustainable Supply Chain Practices; Sürdürülebilir Tedarik Zinciri Uygulamaları; Yeşil Tüketici Davranışı